PERBANDINGAN SISTEM KENDALI SUHU INKUBATOR BAYI DENGAN METODE ZIEGLER-NICHOLS DAN METODE TUNING COHENG-COON - Zulfaniar, Zulfaniar; Aulia, Nur (Universitas Islam Negeri Alauddin Makassar, 2020)
In the world of helath, especially in the handling of newborns, an incubator is one of the right instruments to evercome the problems in handling newborns, newborns cannot produce body heat naturally. Which makes the stability of the body of a newborn is disrupted. So one of the important parameters to be controlled in this probem is the incubator room temperature conditions. The baby incubator is used to get the effect of heat on the baby body. The system that has been used in the incubator to date is still simple, with the aim of using a control system ini making comparisons of 2 methodes is the tuning coheng-coon method and the zegler Nichols method. Obtained respectively the values of Pi, Ki and Kd in the tuning coheng-coon method are 157, 48 and 3.27 and the Ziegler Nichols method respectively the Pi, Ki and Kd constant are 90, 50 and 0 with the resultang constant values capable of of producing a very small error state value of more than 1% at each set point that uses the tuning coheng-coon method so that the method has the advantage of a faster response.Â